2017
DOI: 10.1038/ncomms15995
|View full text |Cite
|
Sign up to set email alerts
|

Quantized circular photogalvanic effect in Weyl semimetals

Abstract: The circular photogalvanic effect (CPGE) is the part of a photocurrent that switches depending on the sense of circular polarization of the incident light. It has been consistently observed in systems without inversion symmetry and depends on non-universal material details. Here we find that in a class of Weyl semimetals (for example, SrSi2) and three-dimensional Rashba materials (for example, doped Te) without inversion and mirror symmetries, the injection contribution to the CPGE trace is effectively quantiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
577
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 607 publications
(594 citation statements)
references
References 56 publications
(82 reference statements)
13
577
2
2
Order By: Relevance
“…Similarly to Ref. [7], one can show that, under the circularly polarized excitation, the polarizationdependent contribution to the square modulus of the matrix element is proportional to the Berry curvature…”
Section: Gyrotropic Crystals In the Absence Of A Magnetic Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to Ref. [7], one can show that, under the circularly polarized excitation, the polarizationdependent contribution to the square modulus of the matrix element is proportional to the Berry curvature…”
Section: Gyrotropic Crystals In the Absence Of A Magnetic Fieldmentioning
confidence: 99%
“…In the theoretical works [7][8][9] the CPGE is studied in the Weyl semimetals. It is established that the contribution of each Weyl node to the circular photocurrent takes the universal form [7] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Weyl points are monopole sources or drains of the Berry curvature of Bloch wave functions in momentum space, a WSM can exhibit an anomalous Hall effect when breaking the time-reversal symmetry (TRS) [17][18][19] or a spin Hall effect [20], as a linear response to an external electric field. Recent theoretical [21][22][23][24][25][26][27][28][29][30] and experimental [31][32][33][34] studies have revealed giant nonlinear optical responses in inversion-symmetry-breaking WSMs, such as the photocurrent from the circular photogalvanic effect (CPGE), second harmonic generation (SHG), and nonlinear Hall effect. These nonlinear effects can be much stronger in WSMs than traditional electro-optic materials owing to the large Berry curvature [22,35,36].…”
mentioning
confidence: 99%
“…Their unique topological properties are predicted to give rise to a wide range of exotic transport and optical phenomena [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. By considering various rotational and mirror symmetries in both symmorphic and non-symmorphic contexts, researchers have predicted nodal-line semimetals [38] [48][49][50].…”
mentioning
confidence: 99%